Jiuding capital : private equity firm with Chinese characteristics (B) - Meng, Fei (SAGE knowledge. Cases., 2016)
On April 23, 2014, Beijing Tongchuang Jiuding Investment Management Co., Ltd. (hereinafter "JD Capital"), the parent company of Jiuding Investment Management Co., Ltd., was listed on China's share transfer system (also known as the New OTC Board or New Third Board; JD Capital's stock code is 430719). It was the first private equity (PE) firm in China to become publicly traded. JD Capital's net assets reached 3.64 billion RMB upon completion of this issuance. Established in 2007, JD Capital had been able to quickly gain a strong foothold in China's private equity market by massively investing in pre-IPO deals and taking advantage of the high valuation offered by the ChiNext Board. JD Capital engaged in a 'factory-style' operational model. This case study discusses this topic.